Sex determination from hand dimensions for forensic identification - Dey, Sangeeta; Kapoor, A. K. (International Journal of Research in Medical Sciences, 2017)
Background: Sex determination is an important and foremost criteria in establishing the identity of an individual. The issue of Sex discrimination can be very complicated in cases of intersex, bodies in advanced state of putrefaction, mutilated & fragmentary remains in which it is common to recover dismembered & peripheral parts of the body. It was realized that anthropometric measurements of the hand has been very useful tool in sexual identification. Objectives: This paper attempts to discriminate between male and female on the basis of hand dimensions, to investigate among the variables which can better predict sex, to derive sectioning point for discriminating sex and to reflect frequent hand index category among the sexes. Methods: The research study was based on 182 subjects (91 males & 91 females) within age 18-60 years, devoid of any deformity, fracture or surgical proceedings of either hand were randomly selected from Udaipur district of Rajasthan. Hand Length and Hand Breadth was obtained from each subject and results were analyzed using IBM SPSS computer software. Results: Hand length and hand breadth show statistically significant male – female differences at p<0.001. Hand Breadth was found as best predictor of sex in comparison with hand length. Frequency of hand index categories reveals that females have highest dolichocheir morphology of hand. Sectioning point analysis confirms that cut-off point of 43 and below is suggestive of male hand whereas above 43 were considered as female hand. Conclusions: This study has implications in mass disasters and in criminal cases where an isolated hand is recovered and needs forensic identification.